KEPASTIAN HUKUM KEWENANGAN PENYIDIK KOMISI PEMBERANTASAN KORUPSI PASCA PERUBAHAN STATUS MENJADI APARATUR SIPIL NEGARA THE LEGAL - Wijonarko, Reqi Endar; Mau, Hedwiq Adianto; Candra, Mardi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The revision of the KPK Law caused another polemic, where Constitutional Court Decision Number 36/PUU-XV/2017 interpreted in essence that the independence and freedom of the KPK from the influence of any power is in carrying out its duties and authorities, which may not be based on the influence or pressure of any party. But the lawmakers instead narrowed the scope of KPK employees by changing the status of KPK employees to Civil Servants (ASN). This is because as ASN employees, KPK employees must also comply with Law Number 5 of 2014 concerning Civil Servants, where the President as the holder of government power is the highest authority in the policy, professional development, and management of ASN. The problem formulation in this thesis is: What is the form of the authority of KPK investigators after the enactment of Law Number 19 of 2019? What is the legal certainty regarding the independence of the authority of KPK investigators after the enactment of Law Number 19 of 2019?. The research method in this thesis consists of: This type of research is normative legal research, which is a legal research approach that focuses on the study of applicable positive legal norms. This method is carried out by examining various relevant laws and regulations, legal doctrines, legal principles, and court decisions, in order to understand how the law should be applied in resolving a problem. The results of this thesis research are: 1) That the authority of KPK investigators as well as the legal certainty and independence of the KPK after the Amendments to Law Number 19 of 2019 have fundamentally shifted the paradigm of legal certainty and the independence of the authority of KPK investigators. If previously legal certainty was based on the principle of lex specialis which gave extraordinary authority and full autonomy, then after the 2019 Law, that legal certainty is no longer absolute, but is bound by a more complex bureaucratic and supervisory framework. The change in the status of investigators to Civil Servants (ASN) theoretically places the KPK in the executive power hierarchy system, which has the potential to harm the principles of institutional and functional independence. Authority that was once guaranteed by internal autonomy is now faced with the potential for intervention and conflicts of interest inherent in the state civil servant structure. Meanwhile, the licensing mechanism by the Supervisory Board (Dewas) reduces procedural legal certainty in terms of the speed and secrecy of the investigation. This is contrary to the essence of law enforcement against extraordinary crimes such as corruption, which demands swift action without bureaucratic obstacles. That the legal certainty regarding the independence of the authority of KPK investigators after the enactment of Law Number 19 of 2019, if previously the KPK functioned as an independent institution with extraordinary authority that could not be intervened, now its legal certainty is no longer absolute. This change creates legal uncertainty and the potential for weakening through the granting of authority to issue SP3 (Warrant for Termination of Investigation) which has the potential to erode the principle of